Dynamic Virtual Resource Allocation for 5G and Beyond Network Slicing; IEEE Open Journal of Vehicular Technology; Vol. 1 - Song Fey; Li Iyun; Ma Chuan; Chzhan Itszin; Shi Long; Dzhayakodi (Jayakody) Arachshiladzh D. N. K. Dushanta Nalin Kumara (2020, 2020)
Title screen